2021
DOI: 10.3390/atmos12020163
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Annual Changes in Heat Stress Occurrence and Its Circulation Conditions in the Polish–Saxon Border Region

Abstract: Heat stress is one of the most critical factors affecting human life. In Central Europe, its influence is noticeable, especially in the Polish–Saxon region, which is a very popular tourist region also inhabited by a high number of elders. The main goal of this paper was to assess multi-annual changes in heat stress occurring in the region, considering the frequency of heat days, the UTCI (Universal Thermal Climate Index), and circulation conditions. The research showed that all the thermal and biothermal indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 61 publications
(132 reference statements)
6
10
0
Order By: Relevance
“…In the cold season, slight, moderate, and strong cold-stress categories were predominant. Similar conditions are typical for the regions located in the lowlands and the lower mountain zones of Poland and Central Europe [10,23,48,50,51,53,54,[66][67][68][69][89][90][91]. The analysis carried out in the paper showed that the frequency of moderate heat stress in July and August in the lower hypsometric zones of Kłodzko Land was about 5% lower than in the Carpathian region, confirming the results of the previous studies [48].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the cold season, slight, moderate, and strong cold-stress categories were predominant. Similar conditions are typical for the regions located in the lowlands and the lower mountain zones of Poland and Central Europe [10,23,48,50,51,53,54,[66][67][68][69][89][90][91]. The analysis carried out in the paper showed that the frequency of moderate heat stress in July and August in the lower hypsometric zones of Kłodzko Land was about 5% lower than in the Carpathian region, confirming the results of the previous studies [48].…”
Section: Discussionsupporting
confidence: 86%
“…The research showed that one of the most important weather factors is heat stress, for which a rising tendency was observed for both indices-heat days and UTCI. The mean frequency of heat days in the lower hypsometric zones amounted to more than 3 days a year, which was comparable to the number observed in the lower mountain zone of the Western Sudety [68], the Silesian Foothills (southern Poland) [84], and in the coastal regions of Germany and Poland [22,24,88]. The multiannual changes indicated that heat-stress frequency has significantly risen over the last decades and can intensify in the following years.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations